1999
DOI: 10.1029/1998jb900056
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of granular shear zones using the distinct element method: 1. Shear zone kinematics and the micromechanics of localization

Abstract: Abstract. Two-dimensional numerical simulations were conducted using the distinct element method (DEM) to examine the influences of particle size distribution (PSD) and interparticle friction /at, on the nature of deformation in granular fault gouge. Particle fracture was not allowed in this implementation but points in PSD space were examined by constructing assemblages of particles with self-similar size distributions defined by the twodimensional power law exponent D. For these numerical "experiments," D ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
218
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(235 citation statements)
references
References 48 publications
(74 reference statements)
9
218
0
Order By: Relevance
“…[7] In this paper we use a traditional DEM approach similar to that presented by Cleary and Campbell [1993]; Campbell et al [1995]; Morgan [1999]; Morgan and Boettcher [1999], based on an existing two-dimensional DEM application [Rege, 1996;Williams and Rege, 1997].…”
Section: Discrete Element Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In this paper we use a traditional DEM approach similar to that presented by Cleary and Campbell [1993]; Campbell et al [1995]; Morgan [1999]; Morgan and Boettcher [1999], based on an existing two-dimensional DEM application [Rege, 1996;Williams and Rege, 1997].…”
Section: Discrete Element Methodsmentioning
confidence: 99%
“…[6] This work investigates hydromechanical behavior of porous media using a DEM technique for solid mechanics first presented by Cundall [1971] and Cundall and Strack [1979], which has successfully approximated the behavior of noncohesive, granular systems under low stress conditions [Cundall et al, 1982;Cleary and Campbell, 1993;Campbell et al, 1995;Morgan, 1999;Morgan and Boettcher, 1999], and lithified sedimentary rocks [Bruno and Nelson, 1991;Potyondy et al, 1996;Hazzard et al, 2000;Boutt and McPherson, 2002]. Extensive comparisons of the DEM to theoretical, numerical, and experimental systems have been performed [Pande et al, 1990].…”
Section: Modeling Approachmentioning
confidence: 99%
“…Two-D DEM simulations (e.g. MORGAN, 1999) also suggest that grain size distribution may influence friction. In addition, it has been shown that grain shape has a first order influence of the sliding friction of the fault gouge.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that these stress waves may effect rock fracture on all scales from microcrack formation to fault slip around mine workings [Hildyard et al, 1995] The distinct element method has been used successfully to examine several different geological applications. Shear band formation in granular material has been examined in depth [Antonellini and Pollard, 1995;Cundall, 1989;Morgan and Boettcher, 1999], earthquake faults with gouge have been simulated [Mora and Place, 1998], and Donz• et al [1996] have used it to model an explosive source in a brittle rock mass. However, there is less published information on the use of distinct element codes to simulate failure of fully competent rocks under compression.…”
Section: Introductionmentioning
confidence: 99%